Analisis Kontrastif Kelas Kata Verba Bahasa Indonesia dan Melayu pada Kamus Bahasa Indonesia dan Bahasa Melayu - Binya, Fadlee (utile: Jurnal Kependidikan, 2024)
Comparative analysis is a branch of linguistics that compares two or more languages ​​to find similarities or differences in form and meaning. Indonesian and Malay have differences and similarities in form or meaning. Furthermore, the aims of this research are, 1) to describe the formation of verb word classes in Indonesian and Malay dictionaries; 2) Describe the similarities and differences of verb classes in Indonesian and Malay dictionaries. Contrastive analysis research uses a qualitative descriptive method. Data collection techniques in this study were carried out through observation, comparative analysis of class statements and documents. Data analysis techniques involve collecting all data, classifying and analyzing the results. The results of the analysis carried out by the author focus on the class of verbs in the Indonesian and Malay dictionaries by comparing their similarities, differences and similarities. Keywords: Analysis of contrasts, verb class, dictionary, meaning, and form